Evaluasi Pengendalian Internal Siklus Pendapatan Pada PT X - Aries Wicaksono (Binus Business Review, 2013)
This study aims to evaluate the implementation of internal control in revenue cycle, to identify weaknesses and limitations of internal control, and to suggest improvements as needed. Research was carried out by using several methods. First, the method of data collection was conducted with internal control questionnaires of revenue cycle, interview, and observation. Second, the method of analysis was performed by using COSO internal control framework. Results obtained are internal control in the revenue cycle applied to the company in general is quite good; and there are ineffective implementation of internal control which can lead to the emergence of risks that could harm the company.